PEDAGOGICAL SOLUTIONS FOR DEVELOPING SELF-AWARENESS AND SELF-ASSESSMENT ABILITIES IN THE EDUCATIONAL PROCESS - Matkarimova Zebiniso Po’latbek qizi (Prospects for innovative technologies in science and education, 2025)
This article covers the theoretical and methodological foundations of the processes of forming, assessing and developing personal consciousness and self-assessment skills in the educational process. The role of modern pedagogical approaches, psychological diagnostic methods, observation, interview, experience and test-based assessment systems in the educational process is analyzed. The opportunities created by the educational environment for the development of a person's creativity, logical thinking, self-assessment, social and technical abilities are highlighted, and effective pedagogical conditions are justified.